Dossier The XI Workshop on Formal Linguistics - Quadros Gomes, Ana Paula; Foltran, Maria José; Pires de Oliveira, Roberta (Revista Letras, 2017)
Apresentação do Dossier The XI Workshop on Formal Linguistics